The quality of hotel service and its impact on improving the level of strategic performance-An exploratory study of the opinions of a sample of employees in premium class hotels in the city of Baghdad (Czech Journal of Multidisciplinary Innovations, 2023)
The current research aims to determine the hotel service quality standard in improving the strategic performance level of the first-class hotels in the city of Baghdad. It relied on the descriptive analytical approach and relied on the questionnaire to obtain the necessary data, which included (32) items by which the variables investigated in the hotels were measured. It also relied on statistical methods (confirmative factor analysis, Arithmetic mean, standard deviation, and coefficient of variation) and the research was applied to an intentional sample of (50) managers of divisions and departments. Through the research, several conclusions were reached, the most important of which is that the quality of service directly affects strategic performance. The study came out with a set of recommendations, the most important of that is the need to improve the level of interest of the researched hotels in their strategic performance, through improving their investment of resources , capabilities and harnessing them better to achieve their goals